Trajectories of Self-Rated Health of Chinese Elders: A Piecewise Growth Model Analysis - Li, Guangming; Hou, Guiyun; Xie, Guohong; Yang, Dong; Jian, Hu; Wang, Weijun (Frontiers in Psychology, 2019)
This study used piecewise growth modeling to describe the developmental trajectories of self-rated health (SRH) in the elderly and longitudinal associations with activities of daily living (ADL), educational level, economic status, age, and gender. Data were drawn from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), collected over 12 years (from 2002 to 2014) at five waves. A total of 16,064 Chinese elders (57.4% females) were analyzed. Results showed two phases of development for SRH; specifically, the decreasing trend of SRH was from slow (in the first phase, wave 1 to wave 3) to fast (in the second phase, wave 3 to wave 5). Descriptives showed that the turning point age was at the age of 83.69 (range = 68 to 116, median age = 82 years old). ADL were positively associated with SRH within each time point (wave of data). Female elders had a higher initial state (i.e., worse) of SRH than did male elders, and poorer economic status was associated with worse initial status of SRH.